Super H-Antimagic Total Covering for Generalized Antiprism and Toroidal Octagonal Map - Amir Taimur; Gohar Ali; Muhammad Numan; Adnan Aslam; Kraidi Anoh Yannick (Journal of Mathematics)
Let G be a graph and H⊆G be subgraph of G. The graph G is said to be a,d-H antimagic total graph if there exists a bijective function f:VH∪EH⟶1,2,3,…,VH+EH such that, for all subgraphs isomorphic to H, the total H weights WH=WH=∑x∈VHfx+∑y∈EHfy forms an arithmetic sequence a,a+d,a+2d,…,a+n−1d, where a and d are positive integers and n is the number of subgraphs isomorphic to H. An a,d-H antimagic total labeling f is said to be super if the vertex labels are from the set 1,2,…,|VG. In this paper, we discuss super a,d-C3-antimagic total labeling for generalized antiprism and a super a,d-C8-antimagic total labeling for toroidal octagonal map.